2020
DOI: 10.1155/2020/8031795
|View full text |Cite
|
Sign up to set email alerts
|

Oral Collagen Drink for Antiaging: Antioxidation, Facilitation of the Increase of Collagen Synthesis, and Improvement of Protein Folding and DNA Repair in Human Skin Fibroblasts

Abstract: This work unveils a fish collagen drink for improvement of skin aging. Previous studies frequently discussed the skin aging from the angle of the representative characteristics of collagen loss and the oxidative-induced expression of proteolytic enzymes matrix metalloproteinases (MMPs), but few groups comprehensively investigated the efficacy of oral hydrolyzed collagen for enhancing protein folding and DNA repair as well as improving notable cell behaviors. To delineate the broad perspective on delaying skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Human skin fibroblasts pretreated with 0.125%, 0.25% or 0.5% fish collagen for 24 h were UV-irradiated (10 J/cm 2 ) for 24 h, and cell viability was restored by 7.9%, 22.3% and 28.1%, respectively. Moreover, mitochondrial activity was restored by 30.6%, 16.4% and 36.1%, respectively [ 51 ]. In another cell assay carried out by Han and coworkers, UV irradiation decreased the survival rate of HaCaT cells, illustrated by a total apoptosis rate of 66.8 ± 1.27%.…”
Section: Antiaging Activity Of Peptides From the Oceanmentioning
confidence: 99%
See 1 more Smart Citation
“…Human skin fibroblasts pretreated with 0.125%, 0.25% or 0.5% fish collagen for 24 h were UV-irradiated (10 J/cm 2 ) for 24 h, and cell viability was restored by 7.9%, 22.3% and 28.1%, respectively. Moreover, mitochondrial activity was restored by 30.6%, 16.4% and 36.1%, respectively [ 51 ]. In another cell assay carried out by Han and coworkers, UV irradiation decreased the survival rate of HaCaT cells, illustrated by a total apoptosis rate of 66.8 ± 1.27%.…”
Section: Antiaging Activity Of Peptides From the Oceanmentioning
confidence: 99%
“…After 24 h UV treatment (10 J/cm 2 ), collagen peptides from the hydrolysis of fish collagen protein restore the expression levels of CCT2, CCT5, CCT6A, CCT8, and PINK1 genes to normal levels. The collagen peptides not only enhanced the expression of elastin and collagen and relieved the damage caused by ROS, but also boosted protein folding and DNA repair, lowering the risk of DNA mutation in UV-treated fibroblasts [ 51 ].…”
Section: The Mechanisms Underlying Antiaging Activitymentioning
confidence: 99%
“…Ageing and environmental factors can lead to dermatological conditions including, but not limited to fine lines, wrinkles, dry skin, excessive pore size, skin dyschromia, reduced elasticity, unwanted hair, skin thinning, purpura, actinic keratosis, pruritus, eczema, acne, rosacea, erythema, telangiectasia, actinic telangiectasia, skin cancer and rhinophyma. Oral collagen supplements/drinks have been shown to improve skin hydration and elasticity for older people [51][52][53][54]. Although there are numerous skincare products on the market to improve skin appearance, many consumers are hesitant to use chemically synthesized products they perceive as being environmentally unfriendly or otherwise unsafe.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen drink improved cell viability of UVA irradiated human skin fibroblast (CCD-966Sk), their mitochondrial activity was restored and reactive oxygen species (ROS) production triggered by UVA treatment was reduced. Moreover, collagen drink promoted the expression of SOD1, SOD2, CAT genes, and improved both collagen and elastin production [ 162 ]. In addition, skin-derived peptides from the sutchi catfish P. hypophthalmus showed matrix metalloproteinase (MMP) inhibitory activity [ 163 , 164 ].…”
Section: Fish Byproducts As Source Of High Added-value Compoundsmentioning
confidence: 99%
“…In addition, skin-derived peptides from the sutchi catfish P. hypophthalmus showed matrix metalloproteinase (MMP) inhibitory activity [ 163 , 164 ]. In particular, Lu et al [ 162 ] found that cod skin gelatin hydrolysates were especially active at 0.1 mg/mL inhibiting MMP-1 expression in fibroblasts irradiated with UVB of 20 mJ/cm 2 . Two peptides, GEIGPSGGRGKPGKDGDAGPK and GFSGLDGAKGD, were isolated from these hydrolysates and found to exhibit a significant inhibition of MMP-1, phosphorylated extracellular signal-regulated kinase (p-ERK) and p-p38.…”
Section: Fish Byproducts As Source Of High Added-value Compoundsmentioning
confidence: 99%